2009
DOI: 10.3844/ajavsp.2009.42.48
|View full text |Cite
|
Sign up to set email alerts
|

Stressors Influence on Salmonella enterica Serovar Enteritidis Colonization in Broilers

Abstract: Problem statement: Poultry industry usually exposing birds to a variety of actions and stressors includs fasting for gastrointestinal emptying before transportation and where birds are often exposed to high environmental temperature during the summer months. These environmental stressors may have influences on bird performance and susceptibility to pathogens such as Salmonella enteritidis by altering the intestinal micrbiota and changes in the gut integrity. Approach: This research was conducted to show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Spread of bacteria into the body cavity through the compromised oviduct wall leads to concurrent peritonitis, which is termed salpingoperitonitis (Saif et al, 2003). Environmental stress has been shown to be a factor that may induce colonization of food animals by enteric pathogens, facilitate horizontal transmission of pathogens between animals, increase pathogen shedding (Soliman et al, 2009). Salpingitis a complex condition of chickens associated with various bacterial agents including Escherichia coli (E. coli), Gallibacterium anatis, Staphylococcus spp., Mannheimia haemolytica, Streptococcus bovis and occasionally Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Spread of bacteria into the body cavity through the compromised oviduct wall leads to concurrent peritonitis, which is termed salpingoperitonitis (Saif et al, 2003). Environmental stress has been shown to be a factor that may induce colonization of food animals by enteric pathogens, facilitate horizontal transmission of pathogens between animals, increase pathogen shedding (Soliman et al, 2009). Salpingitis a complex condition of chickens associated with various bacterial agents including Escherichia coli (E. coli), Gallibacterium anatis, Staphylococcus spp., Mannheimia haemolytica, Streptococcus bovis and occasionally Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Both Scanning and Transmission Electron Microscopes (SEM and TEM) have been used widely in the study of intestinal colonization by Salmonellae (Soliman et al, 2009;Ohl and Miller, 2001). The ultrastructural study had been done previously (YashRoy, 2007), by other researchers they explained the invasion mechanisms of a human isolate Salmonella in the chicken ileum, in addition they showed that over 70% of Salmonellae interacting with ileal epithelial cells developed numerous surface blebs of periplasmic extensions designated periplasmic organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Desirable bacteria can also compete with pathogens for nutrients, and produce microbiostatic and microbicidal substances, such as organic acids and bacteriocins ( Pan and Yu, 2014 ; Clavijo and Flórez, 2018 ). However, aberrant microbiotas of chickens subjected to HS have been related to an increased susceptibility to intestinal colonization of Salmonella Enteritidis ( Burkholder et al, 2008 ; Soliman et al, 2009 ). Tsiouris et al (2018) also demonstrated that HS can promote the expansion of Clostridium perfringens in the chicken intestine, becoming a predisposing factor for necrotic enteritis outbreak in flocks reared under hot conditions.…”
Section: Heat Stress Effects On Gut Health Of Chickensmentioning
confidence: 99%
“…Altered GI epithelium morphology (microarchitecture) and enterocyte lifecycle -Digestive and absorptive dysfunctions → ↓ performance Lambert (2009), Song et al (2014), Vaure and Liu (2014), Wang et al (2015), Wideman (2016), Dokladny et al (2016), Alhenaky et al (2017), Awad et al (2017), France and Turner (2017), Ma et al (2018), Wassenaar and Zimmermann (2018) Frontiers in Physiology frontiersin.org…”
Section: Gi Epitheliummentioning
confidence: 99%